Paediatric invasive pneumococcal disease from two tertiary hospitals in Malaysia - Rengasamy, Sithra; Nachiappan, Jeyaseelan; Borhan, Rohaizah; Othman, Norlijah (Malaysian Medical Association, 2020)
Introduction: Invasive pneumococcal disease (IPD) a leading cause of death and morbidity in children below five-yearsold. This study aims to compare the varied presentation and clinical course of IPD in two different tertiary hospitals in Malaysia. Methodology: A retrospective study of all positive Streptococcus pneumoniae isolates consistent with invasive disease from children below 14 years of age hospitalised in two tertiary hospitals; between year 2012 and 2016 was conducted. IPD cases were defined as isolates of S. pneumoniae from a normally sterile body fluid site. Results: Fifty-four patients were identified in both centres, 35 (65%) from HRPB as compared to 19 (35%) from HS. Majority of cases (14/35, 40 %) in HRPB were of Orang Asli in comparison to Malay children (16/19, 84%) in HS. Septicaemia, pneumonia and meningitis were the most common clinical presentation of IPD in both centres. There was a noticeably higher percentage of isolates found to be non-susceptible (NS) in HS (62.5%) as compared to HRPB (37.5%) although of no statistical significance. Mortality rate was higher in HRPB (26%) in comparison to 11% in HS. Conclusion: This study highlighted the varied presentation of IPD in two different hospital settings. Although both deemed as urban centres, this study emphasises the importance of understanding socio-demography, health facility availability and primary care practices as it significantly alters the clinical course of a disease.